2011
DOI: 10.1021/jp2041857
|View full text |Cite
|
Sign up to set email alerts
|

The Vaporization Enthalpies of 2- and 4-(N,N-Dimethylamino)pyridine, 1,5-Diazabicyclo[4.3.0]non-5-ene, 1,8-Diazabicyclo[5.4.0]undec-7-ene, Imidazo[1,2-a]pyridine and 1,2,4-Triazolo[1,5-a]pyrimidine by Correlation–Gas Chromatography

Abstract: The vaporization enthalpies of a series of heterocyclic compounds some suspected of showing evidence of a higher degree of self-association in comparison to many other nitrogen heterocycles have been measured both by correlation gas chromatography (CGC) and for comparison by transpiration. The compounds share some structural similarities. They include 2- and 4-(N,N-dimethylamino)pyridine, 1,5-diazabicyclo[4.3.0]non-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,2,4-triazolo[1,5-a]pyrimidine and imidazo[1,2-a]pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…In accordance with our earlier study on furazan derivatives (Sheremetev et al, 2004(Sheremetev et al, , 2006(Sheremetev et al, , 2012(Sheremetev et al, , 2013Suponitsky et al, 2009aSuponitsky et al, , 2009b) the O1-N6 and O1-N5 bond lengths of 1.3929 (12) and 1.3742 (12) Å, respectively, are normal. Bond lengths distribution in triazolopyrimidine core is similar to previously studied triazolopyrimidine derivatives (Lipkind et al, 2011;Shikhaliev et al, 2008;Lokaj et al, 2006;Allen, 2002;Allen et al, 1987).…”
Section: S1 Commentsupporting
confidence: 84%
See 1 more Smart Citation
“…In accordance with our earlier study on furazan derivatives (Sheremetev et al, 2004(Sheremetev et al, , 2006(Sheremetev et al, , 2012(Sheremetev et al, , 2013Suponitsky et al, 2009aSuponitsky et al, , 2009b) the O1-N6 and O1-N5 bond lengths of 1.3929 (12) and 1.3742 (12) Å, respectively, are normal. Bond lengths distribution in triazolopyrimidine core is similar to previously studied triazolopyrimidine derivatives (Lipkind et al, 2011;Shikhaliev et al, 2008;Lokaj et al, 2006;Allen, 2002;Allen et al, 1987).…”
Section: S1 Commentsupporting
confidence: 84%
“…For the synthesis of triazolopyrimidines from enaminopropenones, see: Abdelhamid et al (2012Abdelhamid et al ( , 2013; Behbehani & Ibrahim (2012). For X-ray studies of [1,2,4]triazolo [a]pyrimidines, see: Lipkind et al (2011); Shikhaliev et al (2008); Lokaj et al (2006) and of furazan derivatives, see: Sheremetev et al (2004Sheremetev et al ( , 2006Sheremetev et al ( , 2012Sheremetev et al ( , 2013; Suponitsky et al (2009a,b). For normal values of bond lengths in organic compounds, see: Allen et al (1987) and for a description of the Cambridge Structural Database, see: Allen (2002).…”
Section: Related Literaturementioning
confidence: 99%
“…Concerning the p K a of the carboxylic acids, it is well established that the increase in chain length has a negligible effect on p K a . Literature reports have shown that the trends in p K a of carboxylic acids are similar in other solvents,, and hence there are no reasons to suspect that the relative acid strength of the acids studied will change significantly in the PILs medium.…”
Section: Resultsmentioning
confidence: 95%
“…where p (PIL) is the equilibrium vapor pressure of the PIL at the azeotropic composition, pi* is the vapor pressure of each pure component, acid and base, at T =(306.2±0.1) K, and x i (g) and x i (l) are their molar fraction in gas and liquid phase, respectively; x i (g)= x i (l) at the azeotrope. The equilibrium vapor pressures of the acids and bases, at T =(306.2±0.1) K, were taken from the literature …”
Section: Resultsmentioning
confidence: 99%
“…For mTBD, the experimental data presented in this article were used. Literature data were used for DBN, DBU, and TMG [28][29][30][31][32]. To solve for the parameters, we used the differential evolution solver [17] implemented in the SciPy package [18] for Python.…”
Section: Modeling Using Pc-saft Equation Of Statementioning
confidence: 99%